2019
DOI: 10.1002/mnfr.201800847
|View full text |Cite
|
Sign up to set email alerts
|

Increased Consumption of Virgin Olive Oil, Nuts, Legumes, Whole Grains, and Fish Promotes HDL Functions in Humans

Abstract: Scope To evaluate whether increases in the consumption of cardioprotective food groups (virgin olive oil, nuts, fruits/vegetables, legumes, whole grains, fish, and wine) are associated with improvements in high‐density lipoprotein (HDL) functions in high cardiovascular risk subjects. Methods and Results The association between 1‐year changes in food group consumption and HDL functionality traits in 296 high cardiovascular risk subjects is assessed. Increases in virgin olive oil (10 g d–1) and whole grain consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 13 publications
(31 reference statements)
1
30
0
Order By: Relevance
“…The food groups identified as most effective at increasing HDL-C were nuts, whole grains, fish, and red meats. With the exception of the meat item, this list is consistent with the findings of Hernaez et al [77] with regard to associations of Mediterranean diet foods and HDL functionality, including cholesterol efflux capacity and antioxidant activity.…”
Section: Potential Impact Of Dietary Patterns On Hdl Functional Chsupporting
confidence: 89%
See 1 more Smart Citation
“…The food groups identified as most effective at increasing HDL-C were nuts, whole grains, fish, and red meats. With the exception of the meat item, this list is consistent with the findings of Hernaez et al [77] with regard to associations of Mediterranean diet foods and HDL functionality, including cholesterol efflux capacity and antioxidant activity.…”
Section: Potential Impact Of Dietary Patterns On Hdl Functional Chsupporting
confidence: 89%
“…Hernaez at al. [77] have recently interrogated the associations in this study population between changes in food consumption over one year and the observed change in HDL functions and have estimated the change related to common servings of the foods. The fully adjusted multivariate linear regression models yielded significant associations of key foods in amounts achievable through diet with several HDL functions.…”
Section: Potential Impact Of Dietary Patterns On Hdl Functional Chmentioning
confidence: 99%
“…The literature often suggests that lifestyle and traditional dietary habits unique to the Mediterranean region play a role in the prevention of oxidative- and inflammatory-related pathologies, such as cardiometabolic diseases and cancer [ 23 ]. Olive oil, the main dietary fat in the Mediterranean diet, due to its content of oleic acid (MUFA) and minor constituents, modulate different processes linked to chronic low-grade inflammation [ 24 ]. This view is in contrast to diets rich in SFAs, such as the “meat-based” or “Westernized” diets, which are inductive of inflammatory states [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…An intervention with a traditional MD, in the frame of the PREDIMED study, also increased cholesterol efflux in humans at cardiovascular risk [114]. Specifically, the augmentation of the intake of VOO, whole grain, and fish (achievable through a regular diet) were associated with improvements in the HDL cholesterol efflux capacity in subjects at high cardiovascular risk [115]. PCs and fatty acids are potent ligands of the PPARs family and other nuclear factors involved in RCT.…”
Section: Effects Of Voo and Phenol-enriched Voos On Hdl-mediated Cholmentioning
confidence: 99%